2012
DOI: 10.1038/oby.2012.121
|View full text |Cite
|
Sign up to set email alerts
|

Adipokines, Ghrelin and Obesity‐Associated Insulin Resistance in Nondiabetic Patients with Acute Coronary Syndrome

Abstract: Altered glucose metabolism negatively modulates outcome in acute coronary syndromes (ACS). Insulin resistance is commonly associated with increasing BMI in the general population and these associations may involve obesity‐related changes in circulating ghrelin and adipokines. We aimed at investigating interactions between BMI, insulin resistance and ACS and their associations with plasma ghrelin and adipokine concentrations. Homeostasis model assessment of insulin resistance (HOMAIR)‐insulin resistance index, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 28 publications
1
9
0
Order By: Relevance
“…It is known that obesity and obesity-related changes in plasma leptin and adiponectin contribute to negatively modulate insulin resistance. 24 Likewise, earlier studies have found in obese mice, higher basal levels of plasma insulin than in lean mice, also indicating insulin resistance in both sexes. 6 In this study we found that the concentration of FFA, measured in ad libitum conditions ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…It is known that obesity and obesity-related changes in plasma leptin and adiponectin contribute to negatively modulate insulin resistance. 24 Likewise, earlier studies have found in obese mice, higher basal levels of plasma insulin than in lean mice, also indicating insulin resistance in both sexes. 6 In this study we found that the concentration of FFA, measured in ad libitum conditions ( Fig.…”
Section: Discussionmentioning
confidence: 88%
“…Overnight-fasted blood samples were collected also for control subjects. Part of the study results in a smaller study population, pertaining to the associations between obesity, ACS, insulin resistance and adipose tissue hormones have been reported elsewhere [ 22 ].…”
Section: Methods and Proceduresmentioning
confidence: 99%
“…In obesity, adipose tissues produce proinflamma-tory adipokines such as tumor necrosis factor-alpha (TNF-a), leptin, interleukin (IL-6), monocyte chemoattractant protein-1, resistin , and plasminogen activator inhibitor-1(PAI-1), that counteract adiponectin's function and enhance obesityrelated vascular disease (Ronti et al, 2006;Barazzoni et al, 2012). In addition, oxidative stress is now considered to play a key role in metabolic and vascular derangements with an imbalance arising from exaggerated production and reduced elimination of free radicals (Sena et al, 2017).…”
Section: Introductionmentioning
confidence: 99%